(untitled) (Veterinary Science, 2017)
In a work developed in Argentine, La Pampa Province, Maracó Department, to proved the relationship between the microscopic and macroscopic diagnosis of bovine tuberculosis (BT) which on observed an important quantity (30,20%) that granulomatous macroscopic lesions diagnosed as tuberculosis were negative in the hystopathology diagnosis. The present work was realized to determinate what is the agents that cause this lesions. Which the 46,66% of this cases resulted actinomycosis and wooden tongue. The remainder (53,44%), were lesions compatibles with the mentionated lesions. This findings proved the importance of actinomycosis and wooden tongue as endemic disease for the studied zone